Supporting a Knowledge Base With Evidence Retrieved From Randomized Controlled Clinical Trials: A Case Study - Marly G. F. Costa; Gisele R. Vieira; Cicero F. F. Costa Filho (Journal of Systemics, Cybernetics and Informatics, 2010)

(untitled)
This work describes a methodology based on Evidence-Based Medicine for finding literature-based evidence for a clinical decision support system. As an illustration, we applied this method to parenteral nutrition therapy (PNT). PNT requires expertise and experience and is prone to errors. The Pico's strategy was used to built structured clinical questions, which considered 11 PN clinical indications plus a PN nutrient (amino acid, glucose, lipid, electrolyte, trace elements and vitamins), and an outcome. 211 PICO strategies were structured, and 447 searches at PubMed were performed. The results were classified in levels of evidence and recommendation grades according to criteria of the Oxford Centre for Evidence Based Medicine.